MASALAH EFEKTIVITAS SISTEM SELEKSI CALON MAHASISWA BERDASARKAN PREDIKTOR KEBERHASILAN BELAJAR TARAF INTELIGENSI, PRESTASI BELAJAR DI SEKOLAH MENENGAH ATAS DAN HASIL UJIAN SELEKSI MASUK PERGURUAN TINGGI - Muchkiar Suradinata, - (1983)
Selection of freshmen candidates as a process of institutional decision making in order to obtain freshmen candidates with adequate learning abilities to study at institutions of higher learning faces two basic problems, i.e.: (1) the problem of differentiating between applicants possessing the required qualifications for suc-cessfull study and applicants not possessing these qualifications; and (2) the problem of ranking the applicants from the highest to the lowest in terms of their qualifications. The first problem is related to criteria referring to learning abilities needed to successful study;while the second problem is related to the number of freshmen to be accepted. The answer to the first problem refers to the concept of the effectiveness of freshmen candidates selection system in the sense of estimating accurately the the kinds and the levels of learning abilities needed to successful study, This effectiveness of the selection system can be stated by means of the coefficient predictive validity of the predictor to be used. The answer to the second problem refers to the concept of effectiveness of .the selection system in terms of estimating accurately the level of academic success to be reached. This effectiveness of the selection system can be stated by means of the ratio of academic success. The coefficient of the predictive validity of the predictors for academic achievement and the ratio of academic success consist of two out of three parameters for the effectiveness of the freshmen candidates selection system. The third parameter is the selection of freshmen candidates